Mind the gap: Smart Cities and entrepreneurship policies - Santos, Domingos (2018)
The concept of the smart city gained increasing expression and has become an intensely discussed field in the recent past among, either the research community, either the political stakeholders. Yet, despite its semantic attractiveness, the concept still lacks definitional rigor and precision. In particular, if a special focus has been given to the role ICT interventions can fulfill, emphasising its high-Tech characteristics, little attention has been paid to complementary dimensions that are decisive to upgrade urban dynamics competitiveness and sustainability, namely the contribution brought by entrepreneurship. This paper aims, first, to contribute to clarify the meaning of the word "smart" in the context of urban development through an approach based on an indepth literature review of relevant studies and then, to establish the links with the determinants of entrepreneurship that can help guide more effective urban development policies. Furthermore the paper aims to inform and improve policy-making on the subject of promoting entrepreneurial mindsets and contexts, speculating on some principles and guidelines that may help fertilize urban dynamics and build smarter cities.